2019
DOI: 10.1007/s10533-019-00632-y
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between labile carbon, temperature and land use regulate carbon dioxide and methane production in tropical peat

Abstract: Tropical peatlands are a significant carbon store and contribute to global carbon dioxide (CO 2) and methane (CH 4) emissions. Tropical peatlands are threatened by both land use and climate change, including the alteration of regional precipitation patterns, and the 3-4°C predicted warming by 2100. Plant communities in tropical peatlands can regulate greenhouse gas (GHG) fluxes through labile carbon inputs, but the extent to which these inputs regulate the temperature response of CO 2 and CH 4 production in tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 60 publications
2
12
0
Order By: Relevance
“…2a). High methanotroph abundance would also imply large CH 4 production, which has previously been reported from both in situ and ex situ studies of CH 4 production/ fluxes (Girkin et al 2018b;Girkin et al, 2018;Sjögersten et al 2011).…”
Section: Peat Botanical Origin and Microbial Community Structuresupporting
confidence: 60%
“…2a). High methanotroph abundance would also imply large CH 4 production, which has previously been reported from both in situ and ex situ studies of CH 4 production/ fluxes (Girkin et al 2018b;Girkin et al, 2018;Sjögersten et al 2011).…”
Section: Peat Botanical Origin and Microbial Community Structuresupporting
confidence: 60%
“…Redox potential is lower in Proximal than in Distal areas, which may be related to increased need of oxygen for living cells in oil palm rhizosphere (Husson, 2013). Redox potential in all the sampling zones in this study was higher than have been observed in a pristine tropical peatland in Peninsular Malaysia (Girkin et al, 2020a), and only the Ditch zone had higher redox potential than oil palm and pineapple intercropping system in the same region (Girkin et al, 2020a). The higher Redox potential in the ditch may be because of the higher water and oxygen availability in that zone (Figure 3).…”
Section: Discussionsupporting
confidence: 41%
“…Root inputs of oxygen varied significantly between species which, combined with different litter chemistry, exerts a key limitation on rates of decomposition. Differences between species are significant in the context of global land use and climate change, as shifts in peatland plant community composition may alter regional patterns of GHG fluxes through changes in root oxygen inputs, and elevated temperatures can drive substantial increases in CH 4 production [45,46]. As a consequence, we propose that plants have an important role in reducing peat CH 4 fluxes through root inputs of oxygen, and should be included in future models of GHG emissions from tropical peatlands.…”
Section: Conclusion and Discussionmentioning
confidence: 98%